Study of the catalyst deactivation of activated carbon loaded with metal catalyst in tar reforming: article - Mohamad Hashimi, Intan Hayati; Abdul Hossain, Mohammad Asadullah; Kasmuri, Nor Hazelah (2017)
Biomass is a promising source of fuel if it treated efficiently. It can be treated through multiple type of treatment in obtaining the fuel such as thermal conversion, anaerobic digestion and fermentation. In thermal conversion, the biomass is treated through combustion, gasification and pyrolyzation. Gasification is a process that uses heat in limited supply of oxygen to treat the biomass to form synthesis gas. However, along with the syngas, there are impurities that have high potential to be a major problem if not treated the impurities effectively. One of the most problematic impurities from the gasification process is tar. The focus of tar treatment through the catalytic cracking is concerned. However, the catalyst used in catalytic can undergo catalyst deactivation. The most popular catalyst deactivation that happen to the carbon based process is coking. Thus, the main objectives of this paper are to regenerate the catalyst by removing the coke and to determine the characteristics of the fresh and regenerated catalyst. Prior to the study, the synthesized catalyst will undergo gasification process first then the tar will be treated in the tar reforming where the catalyst had been loaded. Then, the catalyst will undergo regeneration process by combustion. The catalysts are analyzed to determine the physical characteristics such as surface area, pore volume and pore size. The analysis shows that the surface area, pore volume and pore size for both catalyst have reduced in a moderate manner.